2013
DOI: 10.1016/j.envpol.2013.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium and associated metals in soils and sediments of wetlands across the Northern Plains, USA

Abstract: Cadmium, present locally in naturally high concentrations in the Northern Plains of the United States, is of concern because of its toxicity, carcinogenic properties, and potential for trophic transfer. Reports of natural concentrations in soils are dominated by dryland soils with agricultural land uses, but much less is known about cadmium in wetlands. Four wetland categories – prairie potholes, shallow lakes, riparian wetlands, and river sediments – were sampled comprising more than 300 wetlands across four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 29 publications
4
20
0
1
Order By: Relevance
“…Most heavy metals in freshwater ecosystems complex with organics and are sequestered into the sediments. A recent survey of sediments taken from the Northern Plains in the United States showed that the surface sediments of potholes, rivers and lakes averaged 0.38 mg of Cd per kg dry weight (Jacob et al 2013). Similar levels have been reported in other surveys conducted in the Southeastern United States, China and Central Europe (Cuculic et al 2016; Li et al 2017; Otter et al 2012), although these can be affected dramatically by anthropogenic activity, particularly mining and agriculture (Audry et al 2004; O'Neill et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most heavy metals in freshwater ecosystems complex with organics and are sequestered into the sediments. A recent survey of sediments taken from the Northern Plains in the United States showed that the surface sediments of potholes, rivers and lakes averaged 0.38 mg of Cd per kg dry weight (Jacob et al 2013). Similar levels have been reported in other surveys conducted in the Southeastern United States, China and Central Europe (Cuculic et al 2016; Li et al 2017; Otter et al 2012), although these can be affected dramatically by anthropogenic activity, particularly mining and agriculture (Audry et al 2004; O'Neill et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Sediments in most waterways are also rich in Cd (typically in the range of 0.1 to 0.7 mg/kg dry weight) and the metal enters the food chain via plants and freshwater invertebrates (Cuculic et al 2016; Jacob et al 2013; Li et al 2017; Otter et al 2012). The level currently considered to be safe for human consumption is 7 μg/week/kg body weight (WHO 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potentially toxic metal ions may, in this case, complex with soil particles . Potentially toxic metals had a close correlation with TN and TP (Table ), which are both thought of as non‐point source inputs, suggesting that the potentially toxic metal pollution might be related to agricultural cultivation and fertilization …”
Section: Discussionmentioning
confidence: 98%
“…Franzen et al (2006) showed Cd concentrations in North Dakota soils varying from 0.01 to 0.31 mg/kg. A survey of wetland soils across North Dakota and northern Minnesota shows that they contain an average of 0.38 mg/kg (Jacob et al 2013). The North American Soil Geochemical Landscapes Project (Smith et al 2009, 2013, 2014; Klassen 2009; Woodruff et al 2009) has released data collected as part of a nationwide geochemical sampling of soils.…”
Section: Introductionmentioning
confidence: 99%